Teachers’ Personality, Perfectionism, and Self-Efficacy as Predictors for Coping Strategies Based on Personal Resources - Samfira, Elena Mirela; Paloş, Ramona (Frontiers in Psychology, 2021)
Many psychological constructs as personality, perfectionism, and self-efficacy have been identified to have a strong contribution to teachers' coping strategies, but how these variables collectively predict different types of coping has received little attention. The present study aimed to explore the personal resources (personality traits, perfectionistic strivings, and self-efficacy) which predict teachers' proactive coping strategies. The sample study consisted of 284 pre-service teachers, with ages ranging from 18 to 34 years old (M = 19.9; SD = 2.1). Four hierarchical multiple regression analyses were conducted separately for every proactive coping strategy based on personal resources as criterion variables. Results showed that conscientiousness and openness were predictors for all four coping strategies based on personal resources (proactive, reflective, strategic planning, and preventive coping), extraversion and neuroticism predicted only proactive coping strategies, and agreeableness did not predict any kind of these coping strategies. Planfulness was a predictor for reflective, strategic planning, and preventive coping strategies; striving for excellence predicted only proactive coping, and organization was a predictor only for reflective coping strategies. Self-efficacy predicted the first three proactive coping strategies but preventive coping. Because coping strategies can be learned, knowing what personal resources may help teachers to cope with stressful situations inside and outside the school, training programs could be organized to improve activity and wellbeing in the teaching profession.